Active Observation and Feedback Strategy Model in Al-Qur'an and Hadith Learning at Madrasah Tsanawiyah - Wahyudi, Dedi; Safitri , Ela; Wardani , Anjani Setia Ayu (Indonesian Journal of Research in Islamic Studies, 2025)
Background: Islamic Religious Education, particularly in the study of the Qur'an and Hadith, requires effective strategies to enhance student engagement and understanding of the material. One strategy that can be implemented is Active Observation and Feedback, which enables students to participate actively in both giving and receiving feedback. Objective: This study aims to analyze the application of this strategy in the teaching of the Qur'an and Hadith at Madrasah Tsanawiyah (MTs) Mambaul Ulum, Tejosari. Method: This study uses a case study approach, where data were collected through observation, interviews, and documentation. Result: The Active Observation and Feedback strategy proved effective in increasing student engagement, as students became more active in explaining the material and received feedback from their peers and teachers. Students showed an improved understanding of the lessons. Conclusion: The Active Observation and Feedback strategy can enhance the quality of learning by encouraging active student participation and reinforcing material understanding. Contribution: This study provides new insights into the development of interactive learning methods based on feedback that can be implemented in madrasas to improve student learning outcomes.